Feasibility and Acceptability of a Student-Led Lifestyle (Diet and Exercise) Intervention Within a Residential Rehabilitation Setting for People With Severe Mental Illness, GO HEART (Group Occupation, Health, Exercise And Rehabilitation Treatment) - Korman, Nicole; Fox, Harley; Skinner, Tina; Dodd, Cassandra; Suetani, Shuichi; Chapman, Justin; Parker, Stephen; Dark, Frances; Collins, Cheryl; Rosenbaum, Simon; Siskind, Dan (Frontiers in Psychiatry, 2020)
Purpose: People with severe mental illness (SMI) experience poor physical health and premature mortality, contributed significantly by modifiable lifestyle risk factors such as unhealthy diet, low cardiorespiratory fitness and inactivity. Lifestyle interventions can reduce cardiometabolic risk and confer a range of other positive mental and physical health benefits. We assessed the feasibility, acceptability, safety and preliminary effectiveness of a lifestyle (combined dietary and exercise) intervention lead by senior exercise and dietetics students in a residential rehabilitation setting. Design: Single arm, prospective study evaluating outcomes pre and post a ten-week lifestyle intervention. Method: People with SMI from three rehabilitation units participated in an exercise intervention three times per week combined with a dietary intervention (six individual and group sessions). Primary outcomes were feasibility (recruitment, retention, and participation rates), acceptability and adverse events. Secondary outcomes included functional exercise capacity, volume of exercise, and metabolic markers, psychiatric symptoms, quality of life and attitudes to exercise. Results: 42 participants were recruited, (92% schizophrenia). Intervention feasibility was supported by high levels of recruitment (68%), retention (77%) and participation (70% exercise, 65% dietary sessions); and no serious adverse events. Significant improvements in functional exercise capacity, volume of exercise, general psychiatric symptoms and negative psychotic symptoms occurred. Metabolic markers did not change. Motivation for and perceived value of exercise reduced over ten weeks. Conclusions: A brief pragmatic student-led lifestyle intervention integrated into usual mental health care was feasible, acceptable, safe and could be implemented across two additional rehabilitation sites with improvements in both exercise outcomes and mental health symptoms. Increased frequency of dietary sessions and length of intervention may improve metabolic outcomes. This study highlights challenges associated with maintaining motivation for healthy lifestyles for people with SMI. Longer term investigation of real-world lifestyle interventions is warranted, together with additional interventions that may support people with SMI to sustain motivation to address lifestyle factors.